Contribution of Active and Inactive States of the Human 5-HT4d Receptor to the Functional Activities of 5-HT4-Receptor Agonists - Tadayoshi Mikami; Hiromi Sugimoto; Rie Naganeo; Takashi Ohmi; Toshiyuki Saito; Hiroyuki Eda (Elsevier, 2008)
In the present study, binding affinities of 5-hydroxytryptamine-4 (5-HT4) ligands for the human 5-HT4d receptor were determined using the agonist [3H]5-HT and the selective 5-HT4 antagonist [3H]GR113,808. We also compared the affinity differences between [3H]5-HT binding (KH) and [3H]GR113,808 binding (KL) with their activities as 5-HT4 ligands. Binding studies using [3H]5-HT revealed that the human 5-HT4d receptor has two binding sites, whereas [3H]GR113,808 yielded a single binding site. Additionally, the number of [3H]5-HT binding sites decreased in the presence of guanosine-5'-O-(3-thiotriphosphate) (GTPγS), but the number of [3H]GR113,808 sites did not change. In competitive binding assays, full agonists such as 5-methoxytryptamine and tegaserod showed 2- to 8-fold higher affinities for [3H]5-HT binding (KH) than for [3H]GR113,808 binding (KL) (KH<KL). Conversely, antagonists showed lower affinities for [3H]5-HT binding than for [3H]GR113,808 binding (KH>KL). Finally, partial agonists displayed similar binding affinities for both radioligands (KH = KL). These findings suggest that the equilibrium between active and inactive states of the human 5-HT4d receptor relies on the functional activities of 5-HT4 ligands, and these states affect the affinities of 5-HT4 ligands in the competitive binding assay. Keywords:: 5-hydroxytryptamine-4 (5-HT4) receptor, agonist, antagonist, serotonin, GR113808